On a Double Decker Omnibus to Golders Green. (January 2022) - Cheyette, Bryan
Abstract : My abiding memory of Daniel Boyarin is sitting with him on the top deck of one of London's famous red buses. We were traveling to Golders Green to eat a kosher meal after a conference in central London. It was the summer of 1994, at the height of Western optimism that the Oslo Accords would bring the Israeli-Palestinian conflict to an end. This optimism, however naive, resulted in an extraordinary phenomenon. Closeted Jews in the British academy attended the conference by the hundreds. The late Laura Marcus and I, who organized "Modernity, Culture, and 'the Jew, '" were expecting a handful of specialists along with the invited speakers, such as Daniel Boyarin. Instead, the audience was made up of a rainbow alliance of out-Jews and other others who could no longer fit on a single red bus but needed a fleet of double-deckers. This was a time when a new iteration of Jewish studies—feminist, fluidly gendered, postcolonial, antiracist, anti-Eurocentric—came into being and has, thankfully, influenced future generations of scholars. 2 No less important, it was a time of a momentary and unspoken hope that the world could be healed and that tikkun olam (the "repair of the world") might at long last be on the horizon.